# Factoring Terms by Grouping

How to factor an algebraic expression step-by-step?

Method to factoring algebraic expression by grouping:

(i) From the groups of the given expression a factor can be taken out from each group.

(ii) Factorize each group

(iii) Now take out the factor common to group formed.

Now we will learn how to factor the terms by grouping.

Solved examples of factoring terms by grouping:

1. Factoring of algebraic expression:

(i) 2ax + ay + 2bx + by

Solution:

2ax + ay + 2bx + by

= a(2x + y) + b(2x + y)

= (2x + y) (a + b)

(ii) 3ax - bx - 3ay + by

Solution:

3ax - bx - 3ay + by

= x(3x - b) - y(3x - b)

= (3x - b) (x - y)

(iii) 6x2 + 3xy - 2ax – ay

Solution:

6x2 + 3xy - 2ax – ay

= 3x(2x + y) - a(2x + y)

= (2x + y)(3x – a)

(iv) ax2 - bx2 + ay2 - by2 + az2 - bz2

Solution:

ax2 - bx2 + ay2 - by2 + az2 - bz2

= x2(a - b) + y2(a - b) + z2(a - b)

= (a - b)(x2 + y2 + z2)

(v) am - an + bm – bn

Solution:

am - an + bm - bn

= a(m - n) + b(m - n)

= (m - n) (a + b)

2. Factorize the following algebraic expression:

(i) 6x + 3xy + y + 2

Solution:

6x + 3xy + y + 2

= (6x + 3xy) + (y + 2)

= 3x(2 + y) + 1(2 + y)

= 3x(y + 2) + 1(y + 2)

= (y + 2) (3x + 1)

= (3x + 1) (y + 2)

(ii) 3x3 + 5x2 + 3x + 5

Solution:

3x3 + 5x2 + 3x + 5

= x2(3x + 5) + 1(3x + 5)

= (3x + 5)(x2 + 1)

(iii) x3 + 3x2 + x + 3

Solution:

x3 + 3x2 + x + 3

= (x3 + 3x2) + (x + 3)

= x2(x + 3) + 1(x + 3)

= (x + 3) (x2 + 1)

(iv) 1 + m + m2n + m3n

Solution:

1 + m + m2n + m3n

= (1 + m) + (m2n + m3n)

= 1(1 + m) + m2n(1 + m)

= (1 + m) (1 + m2n)

(v) x - 1 - (x - 1)2 + ax – a

Solution:

x - 1 - (x - 1)2 + ax – a

= 1(x - 1) - (x - 1)2 + a(x - 1)

= (x - 1) [1 - (x - 1) + a]

= (x - 1) [1 - x + 1 + a]

= (x - 1) (2 + a - x)

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles 1. ### Rupees and Paise | Paise Coins | Rupee Coins | Rupee Notes

Dec 04, 23 02:14 PM

Money consists of rupees and paise; we require money to purchase things. 100 paise make one rupee. List of paise and rupees in the shape of coins and notes:

2. ### Months of the Year | List of 12 Months of the Year |Jan, Feb, Mar, Apr

Dec 04, 23 01:50 PM

There are 12 months in a year. The months are January, February, march, April, May, June, July, August, September, October, November and December. The year begins with the January month. December is t…